Exploring affordances and hindrances when indigenous knowledge is integrated in the topic on waves and sound in a Grade 10 Physical Sciences township class - Manyana, Xolani Justice (Rhodes University, Faculty of Education, Department of Education, 2020)
The lack of interest and hence the decline in the number of learners doing Science in schools, is attributed in part to the decontextualised ways in which Science is taught. As an attempt to address this challenge, the new South African National Curriculum Policy Statement (CAPS) encourages Science teachers to use culturally responsive pedagogies through integrating local or indigenous knowledge (IK) in Science lessons to make it accessible and relevant to learners. But, it does not explicitly state how Science teachers should go about enacting this. It is against this caveat that this study aimed at finding out indigenous practices and knowledge in the community and from two community members that could be integrated into the topic on waves and sound in Grade 10 Physical Sciences lessons with the view to establishing its influence (or not) on learners' conceptions and dispositions towards Science. The study was conducted at Buyelembo Combined School (pseudonym), a township school in the Sarah Baartman District, in the Eastern Cape in South Africa. The research participants were 18 Grade 10 Physical Sciences learners, two Physical Sciences teachers and two community members. Data were generated using the learners' group activity, discussions and presentations, observations (participatory observations and lesson observations), stimulated recall interviews and reflections. A thematic and inductive-deductive approach to data analysis was employed to come up with sub-themes and themes. Underpinned by an interpretivist perspective and informed by Vygotsky's socio-cultural theory, a qualitative case study approach was adopted. Additionally, Ogunniyi's Contiguity Argumentative Theory (CAT) was used as an analytical framework. The five cognitive states of CAT were employed to analyse data during the social interactions to surface any contradictions. The findings from this study revealed that there are indigenous practices and knowledge in relation to the sea that can be integrated into the topic on waves and sound in Grade 10 Physical Sciences lessons. However, regarding relevance of those indigenous practices and knowledge to science, the study revealed that the learners found no relevance at all but discussions and argumentation were enhanced. In addition, findings from this study revealed that the learners' conceptions, dispositions, and sense-making in science were influenced positively through using hands-on practical activities when teaching Science concepts. Lastly, the study revealed that the use of mother tongue by the community members, learners and the teachers together with the language of learning and teaching promoted learner talk. Based on the findings of this study, I recommend that there is a need to support teachers on how to integrate indigenous practices and knowledge in their teaching, particularly when teaching Physical Sciences.
Keywords: Physical sciences -- Study and teaching (Secondary) -- South Africa; Physical sciences -- Study and teaching (Secondary) -- South Africa -- Case studies; Ethnoscience -- Study and teaching -- South Africa; Schools -- South Africa -- Curricula; Social change